Understanding the Pathophysiology of Atopic Dermatitis - insights into Immune Dysregulation and Skin Barrier Dysfunction - Maja Kucharska; Kacper Kwiliński; Barbara Wawrzyńska; Marlena Cąkała; Adrian Kruszewski; Natalia Paduszyńska; Anna Dąbrowska; Paulina Przybysz; Monika Szyszka (Nicolaus Copernicus University in Toruń, 2024)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by a disrupted skin barrier and immune dysregulation. The exact pathophysiology of atopic dermatitis despite extensive research remains complex. It includes genetic disorders, a defect in the epidermal barrier, an altered immune response, and disruption of the skin's microbial balance. Recent advances in research have provided deeper insights into the molecular mechanisms including the role of filaggrin mutations, Th2 cytokine-mediated inflammation, and the skin microbiome. Understanding the intricate interplay between these components is crucial for developing targeted therapeutic strategies. Aim of the study: This review provides a comprehensive overview of the current knowledge on the pathophysiological mechanisms underlying AD, highlighting recent advances and areas for future research. Material and methods: Comprehensive literature searches were performed across the main electronic databases of PubMed and GoogleScholar using the keywords: "atopic dermatitis", "eczema pathophysiology", "skin barrier". Conclusions: Atopic dermatitis (AD) is a complex, chronic inflammatory skin disease with a multifaceted pathophysiology involving genetic, immunological, and environmental factors. Recent advances in understanding the molecular mechanisms underlying AD have highlighted the importance of skin barrier dysfunction, immune system dysregulation, and microbial interactions in the disease's progression.